Importance and challenges of hydrothermal technique for synthesis of transition metal oxides and composites as supercapacitor electrode materials. (1st December 2021) - Yadav, Sarita; Sharma, Ambika
Highlights: Metal oxides and their composites synthesized by the hydrothermal technique for supercapacitor electrodes are reviewed. Supercapacitors background with the charge storage mechanism and latest findings are discussed. The best examples based on the hydrothermal process, providing the importance and challenges have been explored. Summarized the present and future potential of this technique, including the merits and demerits. Abstract: Supercapacitor as an electrochemical energy storage device is of huge interest from both research as well as commercial point of view. This unique device is well known for high power density and long cycle life. Therefore, equipped in several applications ranging from miniature portable electronics to hybrid electric vehicles. Electrode materials play a major role in the electrochemical performance of supercapacitors, amongst which transition metal oxides and their composites are the most explored ones. A well-define morphology of electrode materials relies majorly on the synthesis technique used in the fabrication. For example, hydrothermal technique is one such versatile approach for the formation of supercapacitor electrodes. It is inexpensive, simple, eco-friendly, and allows well define crystalline morphologies with various dimensions and definite pore size distributions. Although, the method has been utilized at a large scale in supercapacitor research, very little knowledge has been shared in detail, summarising the background, utility, and scope of this technique. This review in-depth focuses on the esteemed contribution made by this technique in the synthesis of various metal oxides/hydroxides and their composites in supercapacitor research. The best examples, providing performance evaluation with critical aspects have been explored. Also, the merits and demerits of this technique have been highlighted. Exploring the future scope with the current findings of this technology in supercapacitor development is the main purpose of this review. Graphical abstract: Image, graphical abstract